MEMBUDAYAKAN LITERASI PENDIDIKAN ISLAM PADA MASA PANDEMI COVID 19 PADA PEMBELAJARAN ANAK USIA DINI DI KABUPATEN WONOSOBO - Nur Farida; Hidayatu Munawaroh; Salis Irvan Fuadi; Ahmad Khoiri; Fatiatun Fatiatun (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UNSIQ Jawa Tengah, 2022)
The purpose of this study was to obtain information and determine the application of Islamic education literacy culture during the covid 19 pandemic in early childhood learning in Wonosobo Regency. This study uses a qualitative method with the research instrument used being an observation and observation sheet. The location of the study was conducted at PAUD in the Wonosobo district. Based on the results of the study, it was concluded that the application of literacy culture in Early Childhood Education was applied by PAUD teachers in the Wonosobo district. The application is carried out not just by reading, writing, and Islamic storytelling, but students are also invited to observe and observe the surrounding environment with the etiquette of a Muslim, starting from describing, telling, and making their conclusions from what they see. The culture in the Wonosobo district is famous for its religious culture, so PAUD teachers include children's ability to memorize and read short letters in the culture of building literacy skills in students. During the covid 19 period, health protocols in the learning process were still applied and did not reduce the enthusiasm of PAUD teachers in carrying out their social duties as forming the foundation of the future character of the Indonesian nation.